Extreme Short Stature and Severe Neurological Impairment in a 17-Year-Old Male With Untreated Combined Pituitary Hormone Deficiency Due to POU1F1 Mutation - Majdoub, Hussein; Amselem, Serge; Legendre, Marie; Rath, Shoshana; Bercovich, Dani; Tenenbaum-Rakover, Yardena (Frontiers in Endocrinology, 2019)
Background: POU1F1 is an essential transcription factor for the differentiation, proliferation and survival of somatotrophs, lactotrophs, and thyrotrophs. Mutations in the POU1F1 gene are characterized by growth hormone (GH), thyrotropin, and prolactin deficiencies, commonly presenting with growth retardation and central hypothyroidism. Since the first report in 1992, more than 25 mutations have been identified in POU1F1. Case Description: We describe a 17-year-old male who presented to our Pediatric Endocrinology clinic with extreme short stature (height 81.7 cm, −9.3 SD), cognitive impairment, deaf-mutism, and neurological disabilities. L-thyroxine supplemental therapy, which had been initiated at the age of 6 months but ceased due to non-compliance, was reintroduced at presentation. GH therapy was initiated at 19 years of age, resulting in 42 cm linear growth, to a final height of 124 cm. Sequencing of POU1F1 revealed a previously described homozygous insertion mutation—c.580_581insT, p (Thr194Ilefs*7)—in exon 4 causing a frameshift that introduces a stop codon 7 amino acids downstream, leading to a severely truncated protein lacking the homeodomain. Conclusion: This case report sheds light on the natural history of untreated patients with POU1F1 mutations and raises awareness for early diagnosis and adequate treatment of central congenital hypothyroidism and GH deficiency.